Le principe de réciprocité dans la construction et la gestion de partenariats internationaux dans des universités du Québec : perceptions et pratiques de membres du personnel administratif - Uzenat, Morgane; Kamanzi, Pierre Canisius (Canadian Journal of Higher Education, 2023)
The objective of this article is to examine how far the management of internationalization in Quebec universities is characterized by mutuality. Through the analysis of the work of administrative staff in building and managing international partnerships, we examine the practices related to the four goals of mutuality (equity, autonomy, participation and solidarity) in order to identify those that con-cretely contribute to its implementation. An analysis of interviews with nine senior administrators and project managers from three French-language universities and one English-language university suggests a willingness to build transformational partnerships. The findings show a strong commitment to a vision of international partnerships that blends economic and symbolic benefits with social cohesion.